2022
DOI: 10.4103/jfcm.jfcm_136_22
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization and discrimination against people living with HIV/AIDS: Knowledge, attitudes, and practices of healthcare workers in the primary healthcare centers in Madinah, Saudi Arabia, 2022

Abstract: BACKGROUND: There are very few studies in Saudi Arabia on stigmatization and discrimination against people living with HIV/AIDS (PLWHA), a critical step for the prevention and control of HIV. The aim of this study was to assess the level of stigmatization and discrimination against PLWHA by healthcare workers (HCWs) as well as their knowledge, attitude, and practices (KAP). MATERIALS AND METHODS: This cross-sectional study included 182 HCWs at primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…A finding of this study revealed that the prevalence of discriminatory attitudes against people living with HIV/AIDS was 28.19% (95% CI: 27.74%, 28.64%). This finding is lower than the prior studies done in Ethiopia [ 24 , 29 ], sub-Saharan African countries [ 25 ], Zambia [ 26 ], Botswana [ 27 ], and Saudi Arabia [ 28 ]. The possible reason for this variation might be due to socio-cultural variation, study period, and sample size.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…A finding of this study revealed that the prevalence of discriminatory attitudes against people living with HIV/AIDS was 28.19% (95% CI: 27.74%, 28.64%). This finding is lower than the prior studies done in Ethiopia [ 24 , 29 ], sub-Saharan African countries [ 25 ], Zambia [ 26 ], Botswana [ 27 ], and Saudi Arabia [ 28 ]. The possible reason for this variation might be due to socio-cultural variation, study period, and sample size.…”
Section: Discussioncontrasting
confidence: 63%
“…HIV-related stigma and discrimination significantly affect the health, and well-being [ 12 ], willingness to be tested for HIV [ 13 17 ], initiation and adherence to antiretroviral therapy [ 15 , 18 21 ], and quality of life [ 22 , 23 ]. The findings of the prior studies revealed that the prevalence of discrimination against people living with HIV is 62.66% in Ethiopia [ 24 ], 47.08% in sub-Saharan Africa [ 25 ], 30.3% in Zambia [ 26 ], 42% in Botswana [ 27 ], and 50% in Saudi Arabia [ 28 ]. Studies have shown that being younger age, being a rural dweller, having no formal education, have no media exposure, male-headed household, not tested for HIV, lack of comprehensive knowledge about HIV, household wealth index, marital status, internet utilization status, and community level education [ 25 , 29 , 30 ], are factors associated with discriminatory attitudes against people living with HIV/ADIS.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, patients with HIV expressed concerns about pursuing a career and maintaining employment. The fear of discrimination, stigmatization, and potential disclosure of their HIV status can create barriers and anxieties around finding and retaining employment (Alharbi et al, 2022 ). The finding of our study is consistent with the finding study conducted by Imani et al ( 2021 ), where they reported that discrimination against individuals living with HIV is a distressing reality that is often documented in phenomenological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, providing continuing education and training opportunities to medical staff is crucial. 64 This study presents several recommendations based on the qualitative research findings. The recommendations are analysed from multiple perspectives, including the country, healthcare system, families and individuals.…”
Section: Discussionmentioning
confidence: 99%